Imagens e imaginários da profissão de secretariado na revista excelência - Ana Carolina Goncalves Reis (2012)
This thesis aims to analyze the imaginary social discourse and images ethotic and iconic of the secretarial career adviced on the covers of Excellence magazine, Journal of the National Federation of Secretaries - Fenassec. Specifically, this paper aims: I) To identify the ethéand the imaginaries of the employment imposed on the covers of Excellencein the period 2005-2008; and II) To analyze technical, situational and discursive of the imagesthat make up these layers; and III) To examine the linguistic strata of the genre in question, especially as regards locutive acts - considering the hybrid character (text and image) with which it is characterized. As the theoretical-methodologicalframework for dealing with verbal and pictorial data, the grid of images analysis suggested by Mendes (2011) was used. Through the analyzes, the fact that the magazine builds, in some editions, images of the professional secretaryanchored in contemporary imaginary of the corporate world and the profession. However, in other magazine samples - the majority -, the publication reinforces concepts crystallized on the Professional. One can conclude, therefore, that on the one hand, the ethé of efficiency, competence, competitiveness, versatility, knowledgeand productivity, but on the other hand, one can also observe the submission, subservience, friendliness, elegance, good looks and beauty. Moreover, the occupation is represented, according to the covers as a categorically feminim job (there is a minority of men represented), which led us to postulate a reaffirmation of the social discoursiveimaginaries related to gender in this career. One can also notice that Excellenceseeks to deconstruct negative stereotypes of the craft, commonly disseminated through the media, among other things; the clothing of the characters that feature the editions, which is marked by formality. In this regard, one can notice that the clothing points to the formation of imagistic identity that was coined as the secretary (though, ultimately, the identification of the job is not determined). What one can say is that, in general, there is a transitional phase in the hegemony of the imaginary and the images about the profession, because, as in the case of the profession, there are imaginaries and images that tend to weaken themselves, as well as others which tend to strengthen themselves.